2017
DOI: 10.1111/cpr.12360
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential melastatin 4 channel is required for rat dental pulp stem cell proliferation and survival

Abstract: Rat DPSCs have stem cell characteristics and functional TRPM4 channels that are required for proliferation and survival. These data suggest that the shape and frequency of intracellular Ca signals may mediate stem cell proliferation and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…3 ). The larger Ca 2+ load associated with Biodentine may act through increased Ca 2+ entry into the cell, possibly via Cav1.2 L-type Ca 2+ channels 24 , 25 , ORAI1, an essential pore subunit of store-operated Ca 2+ entry (SOCE) channels in stem cells 26 or TRPM4 channels 27 . Increased Ca 2+ entry is followed by intracellular cycling between the cytoplasm, ER Ca 2+ stores and mitochondria in mesenchymal stem cells, thus leading to the observed Ca 2+ dynamics 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…3 ). The larger Ca 2+ load associated with Biodentine may act through increased Ca 2+ entry into the cell, possibly via Cav1.2 L-type Ca 2+ channels 24 , 25 , ORAI1, an essential pore subunit of store-operated Ca 2+ entry (SOCE) channels in stem cells 26 or TRPM4 channels 27 . Increased Ca 2+ entry is followed by intracellular cycling between the cytoplasm, ER Ca 2+ stores and mitochondria in mesenchymal stem cells, thus leading to the observed Ca 2+ dynamics 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Anticancer drugs may involve changes in Ca 2+ signaling [53,54]; moreover, membrane transport proteins contribute to chemoresistance in several types of cancer [55]. Although TRPM4 is nonpermeable to Ca 2+ , Na + influx via TRPM4 decreases membrane potential and results in a decrease in intracellular Ca 2+ signaling in many different cells, including rat dental pulp stem cells, various immune cells, and cancer cells [2,[12][13][14]41,56,57]. However, an increase in SOCE by TRPM4 expression has also been observed [35,58].…”
Section: General Mechanisms Of Trpm4mentioning
confidence: 99%
“…Intraflagellar transport 80 (IFT80) was also shown to play crucial roles in the proliferation of mouse DPSCs via regulating the FGF–PI3K–AKT signaling pathway [ 27 ]. Moreover, transient receptor potential melastatin 4 channel was revealed to be involved in the proliferation and survival of rat DPSCs by controlling intracellular Ca 2+ signals [ 28 ]. Furthermore, Gao et al demonstrated that the growth capacity of PDLSCs was associated with JNK and p38 MAPK pathways, whereas the proliferation of DPSCs appeared to be dependent on ERK1/2 MAPK pathway activation [ 29 ].…”
Section: Self-renewal and High Growth Capacity Of Dpscs And Shedsmentioning
confidence: 99%